A framework for establishing the technical efficiency of Electricity Distribution Counties (EDCs) using Data Envelopment Analysis. (April 2015) - Mullarkey, Shane; Caulfield, Brian; McCormack, Sarah; Basu, Biswajit
Highlights: Six models are employed to establish the technical efficiency of Electricity Distribution Counties. A diagnostic parameter is incorporated to account for differences across Electricity Distribution Counties. The amalgamation of Electricity Distribution Counties leads to improved efficiency in the production of energy. Abstract: European Energy market liberalization has entailed the restructuring of electricity power markets through the unbundling of electricity generation, transmission and distribution, supply activities and introducing competition into electricity generation. Under these new electricity market regimes, it is important to have an evaluation tool that is capable of examining the impacts of these market changes. The adoption of Data Envelopment Analysis as a form of benchmarking for electricity distribution regulation is one method to conduct this analysis. This paper applies a Data Envelopment Analysis framework to the electricity distribution network in Ireland to explore the merits of using this approach, to determine the technical efficiency and the potential scope for efficiency improvements through reorganizing and the amalgamation of the distribution network in Ireland. The results presented show that overall grid efficiency is improved through this restructuring. A diagnostic parameter is defined and pursued to account for aberrations across Electricity Distribution Counties as opposed to the traditionally employed environmental variables. The adoption of this diagnostic parameter leads to a more intuitive understanding of Electricity Distribution Counties.